Penguatan Pendidikan Karakter Anak di Era Digital bagi Guru PAUD/RA/ TPQ di Desa Ngampungan Bareng - Budiman, Budiman; Wahono, Heru Totok Tri; Asmawan, Yudhi Ferdi Andri (Unity Academy, 2025)
The transformation of education in the digital age requires PAUD/RA/TPQ teachers to be able to integrate character values into a contextual and technology-based learning process. However, the reality in the field shows that most teachers still experience difficulties in utilising digital media for character education. Given this situation, this community service activity aims to enhance teachers' understanding and skills in implementing character education that aligns with digital advancements. The method employed is participatory training, which includes theoretical instruction, interactive discussions, and hands-on practice in developing digital learning media for character education. Participants took pre-tests and post-tests before and after the training to measure improvements in understanding. The results show a significant improvement, with an average pre-test score of 58.75 and a post-test score of 87.50. Additionally, feedback on the content, methods, and facilitators was highly positive, with over 90% of participants expressing satisfaction and relevance regarding the training. This activity was attended by 80 participants, with an attendance rate of 96% of the target. Participants' enthusiasm was reflected in their active participation in discussion and practice sessions, as well as their commitment to apply the training outcomes in their respective educational Institutions. Thus, this activity successfully enhanced teachers' competencies in implementing digital-based character education and highlighted the importance of strengthening teachers' roles in addressing current educational challenges.